Degradable high-oxygen-barrier composite membrane as well as preparation method and application thereof
By modifying graphene oxide through click chemical reactions, a three-dimensional structure is formed, which solves the problem of difficulty in degradation of traditional petroleum-based polymers and insufficient barrier properties of polylactic acid, and achieves an efficient gas barrier effect.
Patent Information
- Application Number
- CN202510098009.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-22
AI Technical Summary
Traditional petroleum-based polymer barrier materials are difficult to degrade, resulting in environmental pollution, and pure polylactic acid has shortcomings in gas barrier properties, limiting its application in the packaging field with high barrier requirements.
Through the click chemical reaction of boric acid and hydroxyl group, the modified graphene oxide is efficiently assembled into hybrid graphene oxide in a "side-facing" connection method, forming a three-dimensional structure, and improving its dispersion and barrier properties in the polymer.
The barrier performance of polylactic acid is significantly enhanced under low filling amount, achieving excellent gas barrier effect, and solving the problems of environmental pollution and insufficient barrier performance of traditional materials.
Smart Images

Figure BDA0005253380340000181 
Figure HDA0005253380350000011 
Figure HDA0005253380350000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer nanocomposite films, and specifically relates to a degradable high oxygen barrier composite film and a preparation method and application thereof. Background Art
[0002] Traditional petroleum-based polymer barrier materials are widely used in the packaging field due to their advantages such as good flexibility, easy processing, light weight and low cost. However, these materials are difficult to degrade in the natural environment. A large amount of waste packaging materials generated in engineering projects are usually disposed of by incineration or landfill, which generates a large amount of carbon emissions. At the same time, microplastics entering the natural world seriously harm the environment and ecosystem. With the increasing global attention to sustainable development goals and the advocacy of a low-carbon circular economy, polymers with degradable properties have gradually become the focus of research and application.
[0003] Polylactic acid (PLA) is a bio-based polymer produced from renewable biological resources (such as corn, sugarcane, etc.). It can be degraded by microorganisms in the natural environment and has excellent biodegradability. As a green and environmentally friendly material, PLA can not only effectively alleviate the environmental pollution problems caused by traditional petroleum-based polymers, but also significantly reduce dependence on petroleum resources. It is one of the materials with broad industrial application prospects. However, pure PLA has certain shortcomings in gas barrier properties, which limits its application and development in the field of packaging with high barrier requirements. Therefore, improving the gas barrier properties of PLA is the key to promoting its widespread application.
[0004] As a two-dimensional nanomaterial, graphene oxide (GO) has become an ideal filler for improving the barrier properties of polymers due to its excellent barrier properties, ultra-high aspect ratio and easy modification. However, GO is easy to agglomerate in polymers, which limits its effect on enhancing the barrier properties of polymers. Usually, graphene oxide is hydrophobically modified using its surface epoxy groups or edge carboxyl groups (common modifiers include dodecylamine, polyethylene glycol, etc.) to enhance its dispersibility and thus improve the barrier properties of the composite material. However, traditional technical means have very limited effects on improving the dispersibility of GO in polymers. In addition to the surface chemical properties of GO, the topological structure of GO is another important factor affecting its dispersibility. Therefore, how to further improve the dispersibility of GO in polymers and thus improve the barrier properties of polymers remains to be studied. Summary of the invention
[0005] In order to overcome the problems of environmental pollution and low oxygen barrier performance of existing oxygen barrier films, the primary purpose of the present invention is to provide a degradable high oxygen barrier composite film.
[0006] The hybrid GO, which is efficiently assembled by the modified GO in a "face-to-edge" connection mode based on the click chemistry reaction of boric acid and hydroxyl, has a three-dimensional structure. It can not only effectively inhibit the close stacking between the sheets through the steric hindrance effect, thereby improving its dispersibility in the polymer; it can also extend the diffusion path of gas molecules in multiple dimensions. The combined effect of the two can greatly enhance the barrier properties of the polymer and achieve a significant enhancement of the barrier properties of PLA at a low filling amount (≤1wt%).
[0007] The B-pGO@OH-eGO / PLA composite oxygen barrier film of the present invention can effectively solve the problem of poor barrier properties of current degradable packaging films.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned degradable high oxygen barrier composite film.
[0009] Another object of the present invention is to provide an application of the above-mentioned degradable high oxygen barrier composite film.
[0010] The purpose of the present invention is achieved through the following technical solutions:
[0011] A degradable high oxygen barrier composite film is composited by degradable PLA and hybrid graphene oxide (B-pGO@OH-eGO).
[0012] The hybrid graphene oxide is a three-dimensional structure formed by graphene oxide in a "face-to-edge" connection mode; the mass percentage of the hybrid graphene oxide in the composite film is 0.25-1wt%.
[0013] The B-pGO@OH-eGO is to first introduce a boric acid group on the graphene oxide surface by a ring-opening reaction between the epoxy group on the graphene oxide surface and the amino group in 4-aminophenylboronic acid to obtain B-pGO, and then introduce 1,3-dihydroxyl groups to the graphene oxide edge by an amidation reaction between the carboxyl group on the graphene oxide edge and the amino group in trishydroxymethylaminomethane to obtain OH-eGO, and finally assemble B-pGO and OH-eGO into B-pGO@OH-eGO in a "face-to-edge" connection mode based on a click chemistry reaction between boric acid and hydroxyl groups. The graphene oxide is a single-layer flake graphene oxide (GO) with a sheet diameter of 50nm to 5μm.
[0014] The hybrid graphene oxide (B-pGO@OH-eGO) is obtained by a click chemical reaction of B-pGO and OH-eGO at a mass ratio of 1:2 to 2:1, and the B-pGO is obtained by a reaction of graphene oxide and 4-aminophenylboronic acid at a mass ratio of 1:4 to 10; the OH-eGO is obtained by a reaction of graphene oxide with a carboxyl activator and then with tris(hydroxymethyl)aminomethane at a mass ratio of graphene oxide to tris(hydroxymethyl)aminomethane of 1:2 to 6.
[0015] The method for preparing the above-mentioned degradable high oxygen barrier composite film comprises the following steps:
[0016] (1) dispersing graphene oxide in water, adding 4-aminophenylboronic acid and adjusting the pH, reacting at room temperature, filtering, washing with water, and drying to obtain borated graphene oxide (B-pGO);
[0017] (2) dispersing graphene oxide in an organic solvent, adding a carboxyl activator and reacting at room temperature, then adding tris(hydroxymethyl)aminomethane and heating to react, filtering, washing with water, and drying to obtain hydroxylated graphene oxide (OH-eGO);
[0018] (3) B-pGO and OH-eGO are mixed and dispersed in water, the pH is adjusted and then reacted, and B-pGO@OH-eGO is obtained after filtering, washing, and drying;
[0019] (4) B-pGO@OH-eGO was dispersed in ethanol, and chloroform was replaced to obtain a B-pGO@OH-eGO chloroform dispersion, and PLA was added and mixed evenly to obtain a film-forming liquid, which was molded and cured to obtain a degradable oxygen barrier film.
[0020] Preferably, the graphene oxide in steps (1) and (2) is a single-layer flake graphene oxide (GO) with a flake diameter of 50 nm to 5 μm.
[0021] Preferably, the mass ratio of 4-aminophenylboric acid to graphene oxide in step (1) is 4 to 10:1, more preferably 5:1.
[0022] Preferably, the pH value in step (1) is adjusted to a range of 7 to 9, more preferably 7 to 8.
[0023] Preferably, the reaction time at room temperature in step (1) is 24 to 48 hours, more preferably 24 to 36 hours.
[0024] Preferably, the carboxyl activator in step (2) is N-hydroxysuccinimide (NHS) and 1-ethyl-(3-dimethylaminopropyl) (EDC); the mass ratio of the carboxyl activator NHS, EDC to GO is 0.5-2:0.5-2:1, more preferably 1:1:1.
[0025] Preferably, the reaction time at room temperature in step (2) is 0.5 to 1 h.
[0026] Preferably, the mass ratio of tris(hydroxymethyl)aminomethane to GO in step (2) is 2 to 6:1, more preferably 3:1.
[0027] Preferably, the temperature of the heating reaction in step (2) is 50 to 70° C., more preferably 60° C.; the reaction time is 4 to 12 h, more preferably 6 to 10 h.
[0028] Preferably, the organic solvent in step (2) is dimethylformamide (DMF).
[0029] Preferably, the mass ratio of B-pGO to OH-eGO in step (3) is 1:2 to 2:1.
[0030] Preferably, the pH value in step (3) is adjusted to 7 to 8, more preferably 7.3 to 7.5.
[0031] Preferably, the reaction temperature in step (3) is room temperature; the reaction time is 8 to 18 hours, more preferably 10 to 18 hours.
[0032] Preferably, the concentration of the dispersion obtained by dispersing the graphene oxide in water in step (1), the dispersion obtained by dispersing the graphene oxide in an organic solvent in step (2), and the dispersion obtained by mixing and dispersing B-pGO and OH-eGO in water in step (3) is 1 to 2 mg / mL, more preferably 1 to 1.5 mg / mL. Preferably, the mass concentration of B-pGO@OH-eGO in chloroform in step (4) is 0.2 to 0.5 mg / mL, more preferably 0.375 mg / mL.
[0033] Preferably, the mass ratio of B-pGO@OH-eGO to PLA in step (4) is 2-5:500-800; more preferably 3.75:500.
[0034] Preferably, the membrane-forming liquid in step (4) is first surface cured at room temperature for 24 to 48 hours, more preferably for 24 to 36 hours, and then dried at 30 to 55° C. for 6 to 8 hours.
[0035] Application of the above-mentioned degradable high oxygen barrier composite film.
[0036] Preferably, the degradable high oxygen barrier composite film is used in the field of packaging.
[0037] The core principle of the technology of the present invention: Based on the click chemistry reaction of boric acid and hydroxyl, the modified GO is efficiently assembled in a "face-to-edge" connection mode to form a hybrid GO with a three-dimensional structure. It can not only effectively inhibit the close stacking between the sheets through the steric hindrance effect, thereby improving its dispersibility in the polymer; it can also extend the diffusion path of gas molecules in multiple dimensions. The combined effect of the two can enhance the barrier properties of the polymer to a greater extent, and achieve a significant enhancement of the barrier properties of PLA at a low filling amount (≤1wt%).
[0038] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0039] (1) The high oxygen barrier composite film provided by the present invention is degradable. Compared with traditional petroleum-based polymer films, it can effectively alleviate the pollution problems caused by traditional petroleum-based polymers and the dependence on petroleum resources, and help implement my country's "dual carbon" plan.
[0040] (2) The present invention uses B-pGO@OH-eGO as filler to prepare the PLA composite film, which can maximize the dispersion of GO while extending the gas molecule permeation path in multiple dimensions and has excellent barrier properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of the reaction process of graphene oxide and 4-aminophenylboronic acid.
[0042] Figure 2 Schematic diagram of the reaction process of carboxylated graphene oxide and tris(hydroxymethyl)aminomethane.
[0043] Figure 3 Schematic diagram of the reaction process of B-pGO and OH-eGO.
[0044] Figure 4 Example 1B-pGO L @OH-eGO L (mass ratio 1:1) infrared spectrum. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0046] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. All raw materials, reagents, etc., whose manufacturers are not specified, are conventional products that can be purchased commercially.
[0047] Example 1
[0048] 40 mg GO L(graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 40mL deionized water and ultrasonicated for 1h; 200mg 4-aminophenylboronic acid was added thereto, the pH was adjusted to 7.0 with phosphate buffered saline solution, and the reaction was stirred at room temperature (300rpm) for 24h; after filtering, it was washed three times with deionized water and dried to obtain borated graphene oxide (B-pGO L ); another 40 mg GO L (graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 40mL DMF and ultrasonicated for 1h. EDC and NHS (40mg each) were added thereto and stirred at room temperature (300rpm) for 1h. Subsequently, 120mg tris(hydroxymethyl)aminomethane was added thereto and stirred at 60℃ (300rpm) for 6h. After filtering, it was washed three times with deionized water and dried to obtain hydroxylated modified graphene oxide (OH-eGO L ); Take 15 mg B-pGO L Add it into 10mL of deionized water and ultrasonicate it for 1h to obtain B-pGO. L dispersion (concentration of 1.5 mg / mL); OH-eGO was prepared in the same way L Dispersion (OH-eGO L The concentration is 1.5 mg / mL). L Dispersed droplets added to B-pGO L The dispersion was adjusted to pH 7.3 with phosphate buffered saline solution, stirred at room temperature (300 rpm) for 18 h, filtered, washed three times with deionized water and dried to obtain hybrid graphene oxide (B-pGO L @OH-eGO L (mass ratio 1:1)).
[0049] Example 2
[0050] 40 mg GO L (graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 40mL deionized water and ultrasonicated for 1h; 200mg 4-aminophenylboronic acid was added thereto, the pH was adjusted to 8.0 with phosphate buffered saline solution, and the reaction was stirred at room temperature (300rpm) for 36h; after filtering, it was washed three times with deionized water and dried to obtain borated graphene oxide (B-pGO L ); another 40 mg GO L(graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 40mL DMF and ultrasonicated for 1h. EDC and NHS (20mg each) were added thereto and stirred at room temperature (300rpm) for 1h. Subsequently, 80mg tris(hydroxymethyl)aminomethane was added thereto and stirred at 70℃ (300rpm) for 5h. After filtering, it was washed three times with deionized water and dried to obtain hydroxylated modified graphene oxide (OH-eGO L ); Take 20 mg B-pGO L Add it into 10mL of deionized water and ultrasonicate it for 1h to obtain B-pGO. L (concentration is 2 mg / mL); OH-eGO was prepared in the same way L Dispersion (OH-eGO L The concentration is 1 mg / mL). L Dispersed droplets added to B-pGO L The dispersion was adjusted to pH 8 with phosphate buffered saline solution, stirred at room temperature (300 rpm) for 8 h, filtered, washed three times with deionized water and dried to obtain hybrid graphene oxide (B-pGO L @OH-eGO L (mass ratio 2:1)).
[0051] Example 3
[0052] 30 mg GO L (graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 20mL deionized water and ultrasonicated for 1h; 120mg 4-aminophenylboronic acid was added thereto, the pH was adjusted to 9.0 with phosphate buffered saline solution, and the reaction was stirred at room temperature (300rpm) for 48h; after filtering, it was washed three times with deionized water and dried to obtain borated graphene oxide (B-pGO L ); another 40 mg GO L (graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 40mL DMF and ultrasonicated for 1h. EDC and NHS (20mg each) were added thereto and stirred at room temperature (300rpm) for 0.5h. Subsequently, 120mg tris(hydroxymethyl)aminomethane was added thereto and stirred at 60℃ (300rpm) for 4h. After filtering, it was washed three times with deionized water and dried to obtain hydroxylated modified graphene oxide (OH-eGO L ); Take 10 mg B-pGO L Add it into 10mL of deionized water and ultrasonicate it for 1h to obtain B-pGO. L (concentration is 1 mg / mL); OH-eGO was prepared in the same way L Dispersion (OH-eGO L The concentration is 2 mg / mL).L Dispersed droplets added to B-pGO L The dispersion was adjusted to pH 7 with phosphate buffered saline solution, stirred at room temperature (300 rpm) for 18 h, filtered, washed three times with deionized water and dried to obtain hybrid graphene oxide (B-pGO L @OH-eGO L (mass ratio 1:2)).
[0053] Example 4
[0054] 40 mg GO M (graphene oxide with a sheet diameter of 200-500 nm) was placed in 20 mL of deionized water and ultrasonicated for 1 h; 280 mg of 4-aminophenylboronic acid was added thereto, the pH was adjusted to 7.0 with phosphate buffered saline solution, and the reaction was stirred at room temperature (300 rpm) for 24 h; after filtering, it was washed three times with deionized water and dried to obtain B-pGO M ; Take another 40mg GO L (graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 20mL DMF and ultrasonicated for 1h. EDC and NHS (40mg each) were added thereto and stirred (300rpm) at room temperature for 0.5h. Subsequently, 120mg tris(hydroxymethyl)aminomethane was added thereto and stirred (300rpm) at 50℃ for 12h. After filtering, it was washed three times with deionized water and dried to obtain OH-eGO. L ; Take 10mg B-pGO M Add it into 10mL of deionized water and ultrasonicate it for 1h to obtain B-pGO. M (concentration is 1 mg / mL); OH-eGO was prepared in the same way L Dispersion (OH-eGO L The concentration was 1 mg / mL). M Dispersed droplets added to OH-eGO L The dispersion was adjusted to pH 7.3 with phosphate buffered saline solution, stirred at room temperature (300 rpm) for 18 h, filtered, washed three times with deionized water and dried to obtain hybrid graphene oxide (B-pGO M @OH-eGO L (mass ratio 1:1)).
[0055] Example 5
[0056] Referring to the modification method of graphene oxide in Example 4, 20 mg B-pGO was used. M Replacement 10mg B-pGO M , the other parameters and reaction conditions remained unchanged, and hybrid graphene oxide (B-pGO M @OH-eGOL (mass ratio 2:1)).
[0057] Example 6
[0058] Referring to the modification method of graphene oxide in Example 4, 20 mg OH-eGO L Replacement 10mg OH-eGO L , the other parameters and reaction conditions remained unchanged, and hybrid graphene oxide (B-pGO M @OH-eGO L (1:2)).
[0059] Example 7
[0060] 40 mg GO L (graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 20mL deionized water and ultrasonicated for 1h; 200mg 4-aminophenylboronic acid was added thereto, the pH was adjusted to 8.0 with phosphate buffered saline solution, and the reaction was stirred at room temperature (300rpm) for 30h; after filtering, it was washed three times with deionized water and dried to obtain B-pGO L ; Take another 40mg GO M (graphene oxide with a sheet diameter of 200-500 nm) was placed in 40 mL DMF and ultrasonicated for 1 h. EDC and NHS (40 mg each) were added thereto and stirred (300 rpm) at room temperature for 1 h. Subsequently, 240 mg of tris(hydroxymethyl)aminomethane was added thereto and stirred (300 rpm) at 60 ° C for 6 h. After filtering, it was washed three times with deionized water and anhydrous ethanol and then dried to obtain OH-eGO. M ; Take 10mg B-pGO L Add it into 10mL of deionized water and ultrasonicate it for 1h to obtain B-pGO. L (concentration is 1 mg / mL); OH-eGO was prepared in the same way M Dispersion (OH-eGO M The concentration is 1 mg / mL). M Dispersed droplets added to B-pGO L The dispersion was adjusted to pH 7.5 with phosphate buffered saline solution, stirred at room temperature (300 rpm) for 12 h, filtered, washed three times with deionized water and anhydrous ethanol, and then dried to obtain hybrid graphene oxide (B-pGO L @OH-eGO M (mass ratio 1:1)).
[0061] Example 8
[0062] Referring to the modification method of graphene oxide in Example 7, 20 mg B-pGO LReplacement 10mg B-pGO L , the other parameters and reaction conditions remained unchanged, and hybrid graphene oxide (B-pGO L @OH-eGO M (mass ratio 2:1)).
[0063] Example 9
[0064] Referring to the modification method of graphene oxide in Example 7, 20 mg OH-eGO M Replacement 10mg OH-eGO M , the other parameters and reaction conditions remained unchanged, and hybrid graphene oxide (B-pGO L @OH-eGO M (mass ratio 1:2)).
[0065] Example 10
[0066] 40 mg GO M (graphene oxide with a sheet diameter of 200-500 nm) was placed in 20 mL of deionized water and ultrasonicated for 1 h; 280 mg of 4-aminophenylboronic acid was added thereto, the pH was adjusted to 7.0 with phosphate buffered saline solution, and the reaction was stirred at room temperature (300 rpm) for 24 h; after filtering, it was washed three times with deionized water and dried to obtain B-pGO M ; Take another 40mg GO M (graphene oxide with a sheet diameter of 200-500 nm) was placed in 20 mL DMF and ultrasonicated for 1 h. EDC and NHS (80 mg each) were added thereto and stirred (300 rpm) at room temperature for 1 h. Subsequently, 240 mg of tris(hydroxymethyl)aminomethane was added thereto and stirred (300 rpm) at 60 °C for 6 h. After filtering, it was washed three times with deionized water and anhydrous ethanol and then dried to obtain OH-eGO. M ; Take 10mg B-pGO M Add it into 10mL of deionized water and ultrasonicate it for 1h to obtain B-pGO. M (concentration is 1 mg / mL); OH-eGO was prepared in the same way M Dispersion (OH-eGO M The concentration is 1 mg / mL). M Dispersed droplets added to B-pGO M The dispersion was adjusted to pH 7.5 with phosphate buffered saline solution, stirred at room temperature (300 rpm) for 12 h, filtered, washed three times with deionized water and anhydrous ethanol, and then dried to obtain hybrid graphene oxide (B-pGO M @OH-eGO M (mass ratio 1:1)).
[0067] Embodiment 11
[0068] 40 mg GO S (graphene oxide with a sheet diameter of 50nm to 200nm) was placed in 40mL deionized water and ultrasonicated for 1h until completely dispersed; 400mg 4-aminophenylboronic acid was added thereto, the pH was adjusted to 7.0 with phosphate buffered saline solution, and the mixture was stirred at room temperature (300rpm) for 36h; after filtering, it was washed three times with deionized water and anhydrous ethanol respectively and then dried to obtain B-pGO S ; Take another 40mgGO L (graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 40mL DMF and ultrasonicated for 1h until completely dispersed. EDC and NHS (40mg each) were added thereto and stirred (300rpm) at room temperature for 1h. Subsequently, 120mg tris(hydroxymethyl)aminomethane was added thereto and stirred (300rpm) at 55℃ for 8h. The mixture was filtered, washed and dried to obtain OH-eGO. L ; Take 10mg B-pGO S Add it into 10mL of deionized water and ultrasonicate it for 1h to obtain B-pGO. S (concentration is 1 mg / mL); OH-eGO was prepared in the same way L Dispersion (OH-eGO L The concentration is 1 mg / mL). L Dispersed droplets added to B-pGO S The dispersion was adjusted to pH 7.3 with phosphate buffered saline solution, stirred at room temperature (300 rpm) for 18 h, filtered, washed and dried to obtain hybrid graphene oxide (B-pGO S @OH-eGO L (mass ratio 1:1)).
[0069] Example 12
[0070] Referring to the modification method of graphene oxide in Example 11, 20 mg B-GO S Replacement 10mg B-GO S , the other parameters and reaction conditions remained unchanged, and hybrid graphene oxide (B-pGO S @OH-eGO L (mass ratio 2:1)).
[0071] Embodiment 13
[0072] Referring to the modification method of graphene oxide in Example 11, 20 mg OH-eGO L Replacement 10mg OH-eGO L, the other parameters and reaction conditions remained unchanged, and hybrid graphene oxide (B-pGO S @OH-eGO L (mass ratio 1:2)).
[0073] Embodiment 14
[0074] 40 mg GO S (graphene oxide with a sheet diameter of 50nm to 200nm) was placed in 40mL deionized water and ultrasonicated for 1h until completely dispersed; 400mg 4-aminophenylboronic acid was added thereto, the pH was adjusted to 7.0 with phosphate buffered saline solution, and the mixture was stirred at room temperature (300rpm) for 36h; after filtering, it was washed three times with deionized water and anhydrous ethanol respectively and then dried to obtain B-pGO S ; Take another 40mgGO M (graphene oxide with a sheet diameter of 200-500 nm) was placed in 40 mL DMF and ultrasonicated for 1 h until completely dispersed. EDC and NHS (40 mg each) were added thereto and stirred (300 rpm) at room temperature for 1 h. Subsequently, 240 mg of tris(hydroxymethyl)aminomethane was added thereto and stirred (300 rpm) at 55 °C for 8 h. OH-eGO was obtained after filtration, washing and drying. M ; Take 10mg B-pGO S Add it into 10mL of deionized water and ultrasonicate it for 1h to obtain B-pGO. S (concentration is 1 mg / mL); OH-eGO was prepared in the same way M Dispersion (OH-eGO M The concentration is 1 mg / mL). M Dispersed droplets added to B-pGO S The dispersion was adjusted to pH 7.3 with phosphate buffered saline solution, stirred at room temperature (300 rpm) for 18 h, filtered, washed and dried to obtain hybrid graphene oxide (B-pGO S @OH-eGO M (mass ratio 1:1)).
[0075] Embodiment 15
[0076] 15 mg of B-pGO prepared in Example 1 L @OH-eGO L (mass ratio 1:1) was ultrasonically dispersed in 15 mL of ethanol, and 40 mL of B-pGO was obtained after centrifugation and replacement with chloroform. L @OH-eGO L 2 g PLA was dissolved in B-pGO (mass ratio 1:1) chloroform dispersion (concentration 0.375 mg / mL). L @OH-eGOL (mass ratio 1:1) dispersion was ultrasonicated for 2 h to obtain a film-forming solution.
[0077] The obtained film-forming liquid was poured into the mold, cured at room temperature for 24 h, and then transferred to a vacuum drying oven at 50 °C for 6 h to obtain B-pGO. L @OH-eGO L (mass ratio 1:1) / PLA composite film. Among them, B-pGO L @OH-eGO L (mass ratio 1:1) The mass fraction in the composite membrane is 0.75wt%.
[0078] Example 16
[0079] Referring to the membrane preparation process in Example 15, the B-pGO prepared in Example 2 was used. L @OH-eGO L (mass ratio 2:1) replaces B-pGO L @OH-eGO L (mass ratio 1:1), the other process parameters remain unchanged, and B-pGO is prepared L @OH-eGO L (mass ratio 2:1) / PLA composite film, B-pGO L @OH-eGO L (mass ratio 2:1) The mass fraction in the composite membrane is 0.75wt%.
[0080] Embodiment 17
[0081] Referring to the membrane preparation process in Example 15, the B-pGO prepared in Example 3 was used. L @OH-eGO L (mass ratio 1:2) replace B-pGO L @OH-eGO L (mass ratio 1:1), the other process parameters remain unchanged, and B-pGO is prepared L @OH-eGO L (mass ratio 1:2) / PLA composite film, B-pGO L @OH-eGO L (mass ratio 1:2) The mass fraction in the composite membrane is 0.75wt%.
[0082] Embodiment 18
[0083] 15 mg of B-pGO prepared in Example 4 M @OH-eGO L (mass ratio 1:1) was ultrasonically dispersed in 15 mL of ethanol, and 40 mL of B-pGO was obtained after centrifugation and replacement with chloroform. M @OH-eGOL 2 g of PLA was dissolved in the chloroform dispersion (mass ratio 1:1) (concentration 0.375 mg / mL). The membrane-forming solution was obtained by ultrasonication for 2 h.
[0084] The obtained film-forming liquid was poured into the mold, cured at room temperature for 48 h, and then transferred to a vacuum drying oven and dried at 30 °C for 8 h to obtain B-pGO. M @OH-eGO L (mass ratio 1:1) / PLA composite film. Among them, B-pGO M @OH-eGO L (mass ratio 1:1) The mass fraction in the composite membrane is 0.75wt%.
[0085] Embodiment 19
[0086] Referring to the membrane preparation process in Example 18, the B-pGO prepared in Example 5 was used. M @OH-eGO L (mass ratio 2:1) replaces B-pGO M @OH-eGO L (mass ratio 1:1), the other process parameters remain unchanged, and B-pGO is prepared M @OH-eGO L (mass ratio 2:1) / PLA composite film, B-pGO M @OH-eGO L (mass ratio 2:1) The mass fraction in the composite membrane is 0.75wt%.
[0087] Embodiment 20
[0088] Referring to the membrane preparation process in Example 18, the B-pGO prepared in Example 6 was used. M @OH-eGO L (mass ratio 1:2) replace B-pGO M @OH-eGO L (mass ratio 1:1), the other process parameters remain unchanged, and B-pGO is prepared M @OH-eGO L (mass ratio 1:2) / PLA composite film, B-pGO M @OH-eGO L (mass ratio 1:2) The mass fraction in the composite membrane is 0.75wt%.
[0089] Embodiment 21
[0090] 15 mg of B-pGO prepared in Example 7 L @OH-eGO M(mass ratio 1:1) was ultrasonically dispersed in 15 mL of ethanol, and 40 mL of B-pGO was obtained after centrifugation and replacement with chloroform. L @OH-eGO M 2 g PLA was dissolved in the chloroform dispersion (mass ratio 1:1) (concentration 0.375 mg / mL). Ultrasonication was performed for 2 h.
[0091] The obtained film-forming liquid was poured into the mold, cured at room temperature for 48 h, and then transferred to a vacuum drying oven at 55 °C for 6 h to obtain B-pGO. L @OH-eGO M (mass ratio 1:1) / PLA composite film. Among them, B-pGO L @OH-eGO M (mass ratio 1:1) The mass fraction in the composite membrane is 0.75wt%.
[0092] Embodiment 22
[0093] Referring to the membrane preparation process in Example 21, the B-pGO prepared in Example 8 was used. L @OH-eGO M (mass ratio 2:1) replaces B-pGO L @OH-eGO M (mass ratio 1:1), the other process parameters remain unchanged, and B-pGO is prepared L @OH-eGO M (mass ratio 2:1) / PLA composite film, B-pGO L @OH-eGO M (mass ratio 2:1) The mass fraction in the composite membrane is 0.75wt%.
[0094] Embodiment 23
[0095] Referring to the membrane preparation process in Example 21, the B-pGO prepared in Example 9 was used. L @OH-eGO M (mass ratio 1:2) replace B-pGO L @OH-eGO M (mass ratio 1:1), the other process parameters remain unchanged, and B-pGO is prepared L @OH-eGO M (mass ratio 1:2) / PLA composite film, B-pGO L @OH-eGO M (mass ratio 1:2) The mass fraction in the composite membrane is 0.75wt%.
[0096] Embodiment 24
[0097] Referring to the membrane preparation process in Example 21, the B-pGO prepared in Example 10 was used. M @OH-eGO M (mass ratio 1:1) replace B-pGO L @OH-eGO M (mass ratio 1:1), the other process parameters remain unchanged, and B-pGO is prepared M @OH-eGO M (mass ratio 1:1) / PLA composite film, B-pGO M @OH-eGO M (mass ratio 1:1) The mass fraction in the composite membrane is 0.75wt%.
[0098] Embodiment 25
[0099] 15 mg of B-pGO prepared in Example 11 S @OH-eGO L (mass ratio 1:1) was ultrasonically dispersed in 15 mL of ethanol, and 40 mL of B-pGO was obtained after centrifugation and replacement with chloroform. S @OH-eGO L 2 g PLA was dissolved in the chloroform dispersion (mass ratio 1:1) (concentration 0.375 mg / mL). Ultrasonication was performed for 2 h.
[0100] The obtained film-forming liquid was poured into the mold, cured at room temperature for 24 h, and then transferred to a vacuum drying oven at 50 °C for 7 h to obtain B-pGO. S @OH-eGO L (mass ratio 1:1) / PLA composite film. Among them, B-pGO S @OH-eGO L (mass ratio 1:1) The mass fraction in the composite membrane is 0.75wt%.
[0101] Embodiment 26
[0102] Referring to the membrane preparation process in Example 25, the B-pGO prepared in Example 12 was used. S @OH-eGO L (mass ratio 2:1) replaces B-pGO S @OH-eGO L (mass ratio 1:1), the other process parameters remain unchanged, and B-pGO is prepared S @OH-eGO L (mass ratio 2:1) / PLA composite film, B-pGO S @OH-eGO L (mass ratio 2:1) The mass fraction in the composite membrane is 0.75wt%.
[0103] Embodiment 27
[0104] Referring to the membrane preparation process in Example 25, the B-pGO prepared in Example 13 was used. S @OH-eGO L (mass ratio 1:2) replaces B-eGO S @OH-pGO L (mass ratio 1:1), the other process parameters remain unchanged, and B-pGO is prepared S @OH-eGO L (mass ratio 1:2) / PLA composite film, B-pGO S @OH-eGO L (mass ratio 1:2) The mass fraction in the composite membrane is 0.75wt%.
[0105] Embodiment 28
[0106] Referring to the membrane preparation process in Example 25, the B-pGO prepared in Example 14 was used. S @OH-eGO M (mass ratio 1:1) replace B-pGO S @OH-eGO L (mass ratio 1:1), the other process parameters remain unchanged, and B-pGO is prepared S @OH-eGO M (mass ratio 1:1) / PLA composite film, B-pGO S @OH-eGO M (mass ratio 1:1) The mass fraction in the composite membrane is 0.75wt%.
[0107] Embodiment 29
[0108] 8 mg of B-pGO prepared in Example 4 M @OH-eGO L (mass ratio 1:1) was ultrasonically dispersed in 15 mL of ethanol, and 40 mL of B-pGO was obtained after centrifugation and replacement with chloroform. M @OH-eGO L 3.2 g PLA was dissolved in the dispersion (mass ratio 1:1) and ultrasonicated for 2 h to obtain a film-forming solution.
[0109] The obtained film-forming liquid was poured into the mold, cured at room temperature for 36 h, and then transferred to a vacuum drying oven at 50 °C for 6 h to obtain B-pGO. M @OH-eGO L (mass ratio 1:1) / PLA composite film. Among them, B-pGO M @OH-eGO L(mass ratio 1:1) The mass fraction in the composite membrane is 0.25wt%.
[0110] Embodiment 30
[0111] 10 mg of B-pGO prepared in Example 4 M @OH-eGO L (mass ratio 1:1) was ultrasonically dispersed in 15 mL of ethanol, and 40 mL of B-pGO was obtained after centrifugation and replacement with chloroform. M @OH-eGO L 2 g of PLA was dissolved in the chloroform dispersion (mass ratio 1:1) (concentration 0.25 mg / mL). The membrane-forming solution was obtained by ultrasonication for 2 h.
[0112] The obtained film-forming liquid was poured into the mold, cured at room temperature for 24 h, and then transferred to a vacuum drying oven at 50 °C for 6 h to obtain B-pGO. M @OH-eGO L (mass ratio 1:1) / PLA composite film. Among them, B-pGO M @OH-eGO L (mass ratio 1:1) The mass fraction in the composite membrane is 0.5wt%.
[0113] Embodiment 31
[0114] 20 mg of B-pGO prepared in Example 4 M @OH-eGO L (mass ratio 1:1) was ultrasonically dispersed in 20 mL of ethanol, and 40 mL of B-pGO was obtained after centrifugation and replacement with chloroform. M @OH-eGO L 2 g of PLA was dissolved in the chloroform dispersion (mass ratio 1:1) (concentration 0.5 mg / mL). The membrane-forming solution was obtained by ultrasonication for 2 h.
[0115] The obtained film-forming liquid was poured into the mold, cured at room temperature for 48 h, and then transferred to a vacuum drying oven at 50 °C for 6 h to obtain B-pGO. M @OH-eGO L (mass ratio 1:1) / PLA composite film. Among them, B-pGO M @OH-eGO L (mass ratio 1:1) The mass fraction in the composite membrane is 1wt%.
[0116] In order to further illustrate the effect of the oxygen barrier film prepared by the present invention, composite films were prepared using graphene oxide, dodecylamine-modified graphene oxide (DDA-GO), and polyethylene glycol-modified graphene oxide (PEG-GO) as fillers as comparative examples.
[0117] Comparative Example 1
[0118] 15 mg GO L (graphene oxide with a sheet diameter of 500nm to 1μm) was ultrasonically dispersed in 15mL of ethanol, centrifuged and replaced with chloroform to obtain 40mL of GO L 2 g of PLA was dissolved in the chloroform dispersion (concentration: 0.375 mg / mL), and the membrane-forming solution was obtained by ultrasonication for 2 h.
[0119] The obtained film-forming liquid was poured into the mold, cured at room temperature for 24 h, and then transferred to a vacuum drying oven at 50 °C for 6 h to obtain GO. L / PLA composite film. L The mass fraction in the composite membrane is 0.75wt%.
[0120] Comparative Example 2
[0121] Referring to the film-making process in Comparative Example 1, GO M (Graphene oxide with a sheet diameter of 200 to 500 nm) to replace GO L (graphene oxide with a sheet diameter of 500nm to 1μm), the other process parameters remain unchanged, and GO is prepared M / PLA composite film, in which GO M The mass fraction in the composite membrane is 0.75wt%.
[0122] Comparative Example 3
[0123] Referring to the film-making process in Comparative Example 1, GO S (Graphene oxide with a sheet diameter of 50nm to 200nm) to replace GO L (graphene oxide with a sheet diameter of 500nm to 1μm), the other process parameters remain unchanged, and GO is prepared S / PLA composite film, in which GO S The mass fraction in the composite membrane is 0.75wt%.
[0124] Comparative Example 4
[0125] 40 mg GO L (graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 40mL deionized water, ultrasonicated for 1h, 1.09mmol dodecylamine (DDA) was added thereto, the pH was adjusted to 7.0 with phosphate buffered saline solution, stirred at room temperature (300rpm) for 24h; after filtering, it was washed three times with deionized water and dried to obtain DDA-GO L . Take 15mg DDA-GO L Place in 15 mL of ethanol, centrifuge, and replace with chloroform to obtain 40 mL of DDA-GO L2 g of PLA was dissolved in the chloroform dispersion (concentration: 0.375 mg / mL), and the membrane-forming solution was obtained by ultrasonication for 2 h.
[0126] The obtained film-forming liquid was poured into the mold, cured at room temperature for 24 h, and then transferred to a vacuum drying oven at 50 °C for 6 h to obtain DDA-GO. L / PLA composite film. Among them, DDA-GO L The mass fraction in the composite membrane is 0.75wt%.
[0127] Comparative Example 5
[0128] Referring to the modification method of graphene oxide in Comparative Example 4, GO M (Graphene oxide with a sheet diameter of 200 to 500 nm) to replace GO L (graphene oxide with a sheet diameter of 500nm to 1μm), and the other parameters and reaction conditions remain unchanged to obtain DDA-GO M Referring to the film making process in Comparative Example 4, DDA-GO M Alternative to DDA-GO L , Preparation of DDA-GO M / PLA composite film, in which DDA-GO M The mass fraction in the composite membrane is 0.75wt%.
[0129] Comparative Example 6
[0130] Referring to the modification method of graphene oxide in Comparative Example 4, GO S (Graphene oxide with a sheet diameter of 50nm to 200nm) to replace GO L (graphene oxide with a sheet diameter of 500nm to 1μm), and the other parameters and reaction conditions remain unchanged to obtain DDA-GO S Referring to the film making process in Comparative Example 4, DDA-GO S Alternative to DDA-GO L , Preparation of DDA-GO S / PLA composite film, in which DDA-GO M The mass fraction in the composite membrane is 0.75wt%.
[0131] Comparative Example 7
[0132] 40 mg GO L (graphene oxide with a sheet diameter of 500nm to 1μm) was placed in 40mL deionized water, ultrasonicated for 1h, 1.34mmol α-hydroxy-ω-amino polyethylene glycol was added thereto, the pH was adjusted to 7.0 with phosphate buffered saline solution, and stirred at room temperature (300rpm) for 24h; after filtering, it was washed three times with deionized water and dried to obtain PEG-GOL . Take 15mg PEG-GO L Place in 15 mL of ethanol, centrifuge, and replace with chloroform to obtain 40 mL of PEG-GO. L 2 g of PLA was dissolved in the chloroform dispersion (concentration: 0.375 mg / mL), and the membrane-forming solution was obtained by ultrasonication for 2 h.
[0133] The obtained film-forming liquid was poured into the mold, cured at room temperature for 24 h, and then transferred to a vacuum drying oven at 50 °C for 6 h to obtain PEG-GO. L / PLA composite film. Among them, PEG-GO L The mass fraction in the composite membrane is 0.75wt%.
[0134] Comparative Example 8
[0135] Referring to the modification method of graphene oxide in Comparative Example 7, GO M (Graphene oxide with a sheet diameter of 200 to 500 nm) to replace GO L (graphene oxide with a sheet diameter of 500nm to 1μm), and the other parameters and reaction conditions remain unchanged to obtain PEG-GO M ; Referring to the film-making process in Comparative Example 4, PEG-GO M Alternative to PEG-GO L , Preparation of PEG-GO M / PLA composite film, in which PEG-GO M The mass fraction in the composite membrane is 0.75wt%.
[0136] Comparative Example 9
[0137] Referring to the modification method of graphene oxide in Comparative Example 7, GO S (Graphene oxide with a sheet diameter of 50nm to 200nm) to replace GO L (graphene oxide with a sheet diameter of 500nm to 1μm), and the other parameters and reaction conditions remain unchanged to obtain PEG-GO S ; Referring to the film-making process in Comparative Example 4, PEG-GO S Alternative to PEG-GO L , Preparation of PEG-GO S / PLA composite film, in which PEG-GO S The mass fraction in the composite membrane is 0.75wt%.
[0138] Fourier transform infrared spectroscopy (FT-IR) was used to analyze the graphene oxide modified with 4-aminophenylboronic acid, the graphene oxide modified with trishydroxymethylaminomethane, and the hybrid graphene oxide (B-pGO) of Example 1. L @OH-eGO L(mass ratio 1:1)) and graphene oxide were characterized, and the results are as follows Figure 4 shown.
[0139] The oxygen barrier performance of the composite film is characterized by the oxygen relative permeability coefficient (i.e., the ratio of the composite film oxidation permeability coefficient to the pure PLA film oxygen permeability coefficient). The smaller the composite film permeability coefficient, the better its barrier performance. The oxygen permeability coefficient test is carried out according to the film and sheet gas permeability test method described in GB / T 1038-2000. The control test conditions are: temperature 22°C, humidity 35%, oxygen cylinder pressure 0.4MPa, and the permeability coefficient of the prepared degradable composite film material is measured. The test results are listed in the following table.
[0140] Table 1 Relative oxygen permeability coefficient of composite membrane
[0141]
[0142] The test results show that the hybridized graphene oxide significantly improves the oxygen barrier performance of the composite material. M @OH-eGO L The oxygen barrier performance of (1:1) / PLA composite film is better than that of GO before modification. L / PLA improved by about 78% compared to DDA-GO L / PLA composite film increased by about 53% compared with PEG-GO L The / PLA composite film is improved by about 58%. The composite film prepared by the present invention has excellent oxygen barrier performance.
[0143] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A degradable high oxygen barrier composite film, characterized in that: Composited from PLA and hybrid graphene oxide; And / or, the hybrid graphene oxide is obtained by a click chemistry reaction between borated graphene oxide and hydroxylated graphene oxide; And / or, the borated graphene oxide is obtained by reacting graphene oxide with 4-aminophenylboronic acid; And / or, the hydroxylated graphene oxide is obtained by reacting graphene oxide with a carboxyl activator and then reacting with trishydroxymethylaminomethane.
2. A degradable high oxygen barrier composite film according to claim 1, characterized in that: The mass percentage of the hybrid graphene oxide in the composite film is 0.25-1wt%; And / or, the hybrid graphene oxide is obtained by a click chemistry reaction of borated graphene oxide and hydroxylated graphene oxide in a mass ratio of 1:2 to 2:1; And / or, the borated graphene oxide is obtained by reacting graphene oxide and 4-aminophenylboronic acid in a mass ratio of 1:4 to 10; And / or, the hydroxylated graphene oxide is obtained by reacting graphene oxide, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) in a mass ratio of 1:0.5-2:0.5-2, and then reacting with tris(hydroxymethyl)aminomethane in a mass ratio of graphene oxide to tris(hydroxymethyl)aminomethane of 1:2-6.
3. A degradable high oxygen barrier composite film according to claim 1 or 2, characterized in that: The graphene oxide is a single-layer flake graphene oxide with a flake diameter of 50nm to 5μm.
4. A degradable high oxygen barrier composite film according to claim 1 or 2, characterized in that: The temperature of the click chemistry reaction is room temperature, the pH of the reaction system is 7 to 8, and the reaction time is 8 to 18 hours; And / or, the temperature of the reaction of graphene oxide and 4-aminophenylboronic acid is room temperature, the pH value of the reaction system is 7 to 9, and the time is 24 to 48 hours; And / or, the graphene oxide reacts with the carboxyl activator at room temperature for 0.5 to 1 h; and then reacts with tris(hydroxymethyl)aminomethane at 50 to 70° C. for 4 to 12 h.
5. The method for preparing a degradable high oxygen barrier composite film according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dispersing graphene oxide in water, adding 4-aminophenylboronic acid and adjusting the pH, reacting at room temperature, filtering, washing with water, and drying to obtain borated graphene oxide; (2) dispersing graphene oxide in an organic solvent, adding a carboxyl activator and reacting at room temperature, then adding tris(hydroxymethyl)aminomethane and heating to react, filtering, washing with water, and drying to obtain hydroxylated graphene oxide; (3) mixing and dispersing the borated graphene oxide and the hydroxylated graphene oxide in water, reacting after adjusting the pH, filtering, washing with water, and drying to obtain hybrid graphene oxide; (4) The hybrid graphene oxide is dispersed in ethanol, replaced by chloroform to obtain a chloroform dispersion, and then PLA is added and mixed evenly to obtain a film-forming liquid, which is molded and cured to obtain a degradable oxygen barrier film.
6. The method for preparing a degradable high oxygen barrier composite film according to claim 5, characterized in that: The graphene oxide in steps (1) and (2) is a single-layer flake graphene oxide with a flake diameter of 50 nm to 5 μm; And / or, the mass ratio of 4-aminophenylboronic acid to graphene oxide in step (1) is 4 to 10:1; And / or, the carboxyl activator in step (2) is N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl); the mass ratio of N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl) to graphene oxide is 0.5-2:0.5-2:1; And / or, the mass ratio of tris(hydroxymethyl)aminomethane to graphene oxide in step (2) is 2 to 6:1; And / or, the mass ratio of the borated graphene oxide to the hydroxylated graphene oxide in step (3) is 1:2 to 2:1; And / or, the mass ratio of the hybrid graphene oxide to PLA in step (4) is 2-5:500-800.
7. A method for preparing a degradable high oxygen barrier composite film according to claim 5 or 6, characterized in that: The pH value of step (1) is adjusted to a value between 7 and 9; And / or, the reaction time at room temperature in step (1) is 24 to 48 hours; And / or, the reaction time at room temperature in step (2) is 0.5 to 1 h; And / or, the temperature of the heating reaction in step (2) is 50-70° C.; and the reaction time is 4-12 hours.
8. The method for preparing a degradable high oxygen barrier composite film according to claim 5 or 6, characterized in that: Step (3) wherein the pH is adjusted to 7 to 8; And / or, the reaction temperature in step (3) is room temperature; the reaction time is 8 to 18 hours; And / or, the membrane-forming liquid in step (4) is first surface cured at room temperature for 24 to 48 hours, and then dried at 30 to 55° C. for 6 to 8 hours.
9. A method for preparing a degradable high oxygen barrier composite film according to claim 5 or 6, characterized in that: The concentration of the dispersion obtained by dispersing the graphene oxide in water in step (1) is 1 to 2 mg / mL; And / or, the concentration of the dispersion obtained by dispersing the graphene oxide in the organic solvent in step (2) is 1 to 2 mg / mL; And / or, in step (3), the concentration of the dispersion obtained by mixing and dispersing the borated graphene oxide and the hydroxylated graphene oxide in water is 1 to 2 mg / mL; And / or, the mass concentration of the hybrid graphene oxide in chloroform in step (4) is 0.2-0.5 mg / mL; And / or, the organic solvent in step (2) is dimethylformamide.
10. Use of the degradable high oxygen barrier composite film according to any one of claims 1 to 4.
Citation Information
Patent Citations
Nanometer composite material high in air barrier property and preparation method thereof
CN107541033A
Degradable barrier nano-composite film as well as preparation method and application thereof
CN112831165A
Preparation method of functional graphene oxide based on alcohol-alkyne click reaction
CN117658118A